PERAN MODAL SOSIAL DALAM UPAYA PENGEMBANGAN USAHA MIKRO KECIL MENENGAH (UMKM) NASABAH BTPN SYARIAH KECAMATAN MENGW - NATALANDO, FELIX; NUGROHO, WAHYU BUDI; ADITYA, I GUSTI NGURAH AGUNG KRISNA (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
This study aims to analyze the role of social capital in the development of Micro, Small, and Medium Enterprises (MSMEs) among BTPN Syariah customers in Mengwi District. Social capital, which includes trust, social networks, and shared norms, plays a strategic role in promoting business success. The theoretical framework applied is James Coleman's social capital theory, emphasizing the importance of social relationships, trust, norms, and networks in building the economic capacity of individuals or groups. This research employs a qualitative method, with data collection techniques including in-depth interviews, observations, and documentation involving BTPN Syariah MSME customers. The findings indicate that social capital significantly influences MSME development. The trust established between customers and the bank facilitates access to capital and business mentoring. Social networks among customers create synergy and collaboration in product marketing and information sharing regarding business opportunities. Shared norms, such as mutual support and accountability, strengthen relationships among group members. The study concludes that social capital can be a key factor in enhancing the sustainability and growth of MSMEs, particularly within the context of Islamic banking, which emphasizes social values. The recommendations include enhancing community-based training programs and expanding customers' social networks to foster a more inclusive and competitive business ecosystem.